A Comparative Research Of Water Resources Protection Between Indonesia And Pakistan - Adi Gunawan; Sapto Wahyono; Ach. Rifai; Sofianto; Safitri Wulandari; Febrina Heryanti (IHSA Institute, 2024)
Viewed from the legal aspect, the government’s attention to water resources can be seen from the management, sustainable water resource development, and public participation principles. This research discussed these three aspects by adding the advantages and disadvantages of water resource management in Pakistan. This research was library research with a legislative approach and using comparative research. The research results showed that there were three aspects of water management in Indonesia. The first was the principle that water resources are part of Human Rights. Furthermore, water resources are an important part that cannot be separated from an environmentally friendly sustainable development strategy. Then, community participation was stated in Articles 2, 4, Articles 62, and 63 of Law 17 of 2019. Meanwhile, there were three basic aspects of the management of Pakistan’s water resources. First was the principle of Pakistan’s water management, which was stated in the country’s constitution in 1973 and adopted by the UN Resolution, which ensured fair and equal access to clean water and sanitation for all its citizens. The second aspect of sustainability of the Pakistani government was to establish a planting policy strategy with the concept of More Crops per Drop or more plants per drop, which was continued with national-scale technical actions. At the same time, the third aspect was in terms of public participation. The government stated it in the National Water Policy of 2018. The advantages of Pakistan’s water resource management law were based on Islamic law, the internationalization of water resource management, and the establishment of a special agency that deals with water resources. The weakness of the law was that Pakistan did not have a master law on water resource management that applied nationally. Secondly, there was no national legal update and a tiered water resource management structure that could cause national disparities between regions.